Scientific Foundation For Implementation Of The Compliance Control System At Corporate Enterprises - Suyunov, Dilmurod Kholmuradovich (The American Journal of Management and Economics Innovations, 2021)
The article analyzes the concept of compliance control at corporate enterprises, the views of economists in this area, the principles of compliance control, as well as implementation methods. In addition, the article presents scientifically substantiated conclusions on this issuer.